Adjustable Folding Aluminium Louvres Application on ‘Hop (B): Nob Marina Quay’ - WAHAB, IZUDINSHAH; Anis Najwa Azman,; Hazri Abd Aziz,; Mohd Jamil Mohd Hamberi,; Lokman Hakim Ismail, (Recent Trends in Civil Engineering and Built Environment, 2020)
Natural Ventilation is one of the factors in enhancing the indoor air quality in buildings. Unfortunately, most buildings nowadays are still depending heavily on mechanical ventilation and air conditioning for their daily operations which cause a lot of energy consumption. Based on previous studies, there are mechanisme and systems studied and invented to enhance building natural ventilation especially for tropical area. Therefore, this design studyaims to proposed an application of an adjustable folding aluminium louvres in the ‘HOP (B) : NOB’ Marina Quay in Pulau Pinang. The application may maximize the effect of natural ventilation for the building’s indoor spaces via cross and stack effect ventilation.At the same time, the installation of the adjustable folding louvres may also enhance the façade quality while giving sun shades to the building. The findings of this design study indicate that although natural ventilation is needed in a building, controlling the direction and strong winds inside the building is also essential in order to give the right intensity to the application of natural ventilation in ‘HOP (B) : NOB’ Marina Quay